Penerapan budaya pengenalan lagu nasional dan daerah di lingkungan sekolah sebagai media pengembangan karakter nasionalis siswa - Istifadah, Qonita (Maliki Interdisciplinary Journal, 2023)
The formation of character is inseparable from the role of the world of education where education is expected to build noble ethical values in life, one of which is the nationalist character. The formation of nationalism can be done through cultural habituation in the school environment. One of the implementations is the introduction of the national and regional anthem. The purpose of this study was to determine the urgency of school culture, the role of national and regional songs, and the role of teachers in forming nationalist character. The research method uses descriptive qualitative analysis and the data obtained is based on literature from previous research. The results obtained are an increase in the performance of cognitive tasks and music as a facilitator of the process, this anthem have the impression of inviting all citizens of the nation to do their best for the benefit of the Indonesian. In the results of field trials, the feasibility of songs in character building reached a percentage of 86%. The conclusion of this study is formation of nationalist character in the student environment can be influenced by the role of culture in schools which is by familiarizing the culture of introducing national and regional songs. The teacher’s role in cultivating cultural habits of introducing national and regional songs can be done with the repetition method. intensive interaction, as well as evaluation.